El juego y la motricidad gruesa en los niños de 4 a 5 años de la escuela de educación básica Dr. Reinaldo Espinosa ubicada en la ciudad de Loja, en el período 2019 – 2020. - Sánchez Romero, Luz Verónica (2021)
The present research work refers to: the general objective of analyzing the importance of games in gross motor skills in children of 4 to 5 years, the research design was non- experimental with a mixed approach, The used methods were descriptive, analytical- synthetic and inductive-deductive, to establish the diagnosis we worked with a sample of 15 people, divided into, 14 children and 1 teacher, as a technique we used the interview directed to the teacher , the instrument applied was the Abbreviated Development Scale (SDA-1) by Nelson Ortiz The population studied was 1 teacher and 14 children between 4 and 5 years old. The results obtained indicate that 57% of the children are at a medium level, 36% are at medium high and 7% are on alert. This shows that a moderate percentage of children presented slight difficulties in the development of gross motor activities, thus concluding the design of an activity guide aimed at strengthening the development of gross motor skills, abilities and skills in children aged 4 to 5 years of the Dr. Reinaldo Espinosa School of Basic Education.